The article studies the history of Hungarian emigration to Russia in the 18–20th century - Ptyicin, Andrej Nyikolajevics (Acta Scientiarum Socialium, 2012)
The article studies the history of Hungarian emigration to Russia in the 18–20th century. It shows the social and ethnic composition of emigrants. It emphasizes educational and business activities. The article describes the development of different parts of life in Russia contributed by Hungarian settlers.